The importance of health education for neuropsychosocial rehabilitation in therapeutic communities: experience report (Research, Society and Development, 2023)
Introduction: Chemical dependency is a major social and public health problem. During the treatment conducted in Therapeutic Communities, there is an experiential reflection caused by the removal from drugs and society. Objective: To report the experience in a Therapeutic Community in the Municipality of Lavras-MG, as well as its political challenges, presenting a reflection on the role of these entities in the context of health surveillance and education, and how such interventions can significantly contribute to therapeutic adherence. Method: 38 male patients with an average age of 35 years, who were undergoing treatment, participated in the activities. Health actions were developed in the outpatient field, and approaches in the form of lectures were given, focusing on the health perspectives of individuals in order to address the importance of care and education practices in neuropsychosocial rehabilitation for the patients in treatment. The main hypothesis is that there is a direct relationship between the perception of the future by inmates as they return to a state of well-being. Results: Reflections were linked to the definition of health, the impact of drugs on cognition and aspects of neurological rehabilitation, the individual perception of recovery and the perspective of the future, as well as the challenges faced by the Therapeutic Community in providing health support. Conclusion: During the construction of this report, it was observed that health actions are of fundamental importance in the rehabilitation process of patients undergoing treatment for addiction within Therapeutic Communities.